A companion to North Africa in antiquity - Hitchner, R. Bruce 1947- (Blackwell companions to the ancient world, 2022)
"The historiography on Ancient North Africa is massive and still predominantly in French, though scholarship and archaeological research published in Italian, Spanish, English, German, and Arabic has increased notably since the 1970s. The main challenge facing those who wish to work in the field comes from the association of its historiography with French and Italian colonialism and its legacy. Having conquered and annexed Algeria in the mid-nineteenth century, the French authorities were deeply concerned with the long-term success of their colonial mission, which they saw as continuing in the footsteps of Rome in Africa. One avenue to this end was considerable investment in the discovery and analysis of the process-dubbed Romanisation--by which the Roman state was believed to have imposed its imperial culture and civilization on the polities, peoples, and landscape of the region.